Pertanggungjawaban Korporasi terhadap Tindak Pidana Siber: Analisis Yuridis terhadap Perlindungan Subjek Data Pribadi (Studi Kasus Putusan Pengadilan Negeri Pangkalpinang Nomor Putusan Nomor 142/Pid.Sus/2024/Pn Pgp - Syafrudin Eko Haryanto Kembang Dada; Ina Heliany (FOCUS, 2026)
The development of information technology offers significant benefits but also creates serious risks, particularly concerning security and personal data protection. Cybercrime has therefore become a crucial legal issue, as it may involve not only individuals but also corporations as subjects of criminal law. This study examines: (1) the application of corporate criminal liability in cybercrime under positive law, and (2) whether judicial considerations in Decision Number 142/Pid.Sus/2024/PN Pgp reflect justice and legal protection for personal data subjects. This research employs a normative legal method using statutory and case approaches. The findings show that corporations are recognized as criminal law subjects that can be held liable for cybercrimes, including personal data misuse, through sanctions such as fines and other punitive measures. Criminal liability may be imposed based on direct liability, strict liability, or vicarious liability. In the examined case, the court applied the Personal Data Protection Law as lex specialis and imposed imprisonment and fines after considering aggravating and mitigating factors. This decision affirms that both individuals and corporations are subject to criminal liability and highlights the importance of law enforcement in protecting personal data and combating cybercrime.